PENGEMBANGAN PEMBELAJARAN EKOLOGI HEWAN BERBASIS PROYEK DAN POTENSI LOKAL KAWASAN DANAU TOBA - Retnita Ernayani Lubis; Mimien Henie Irawaty; Ibrohim Ibrohim; Sri Endah Indrawati (Universitas Negeri Medan, 2019)
This research is a development research. The aim of the study was to develop Animal Ecology learning devices based on Project-Based Learning and local Lake Toba to train mastery of concepts, critical thinking, problem solving, and attitudes to students of Biology Education that are valid, practical and effective. The development research used was using the Thiagarajan 4D model. The results showed that in the define stage a mapping of the basic competencies of Animal Ecology was produced and the material of local potential Lake Toba Region and learning objectives were adjusted to the results of the stages defined. The design phase shows the format of the learning device developed. The develope stage shows the results of validation by the validator stating that project-based Animal Ecology learning tools and local potential are declared valid and the results of the student response questionnaire on positive learning devices. The dessiminate stage shows the learning device that was developed effectively. Project-based Animal Ecology learning tools and the resulting local potential of Lake Toba have met the criteria of valid, practical and effective.Keywords. Learning Animal Ecology, Project Based Learning, Local Potential.